Analisis Tanggungjawab Hukum Administrasi Negara dalam Penanganan Korupsi di Sektor Publik - Novita Mayasari Angelia; Lingga Abi Rahman; Maulida Maulida (Jurnal Hukum dan Sosial Politik, 2024)
Corruption is often carried out by individuals who hold power, so that the characteristics of corruption crimes are always related to abuse of authority in the context of organized crime. This article aims to analyze the role of State Administrative Law in handling corruption in the public sector. Using the literature study method, this article collects data from various sources such as books, news and journal articles. The discussion includes the importance of administrative law in limiting and controlling excessive power possessed by state officials, as well as the role of bureaucracy in preventing corruption. In addition, this article outlines the types of legal accountability that apply to government officials involved in corruption, as well as the importance of internal and external monitoring in reducing acts of corruption. The principles of good governance and the need to reform the government system were also raised as important steps in eradicating corruption.